2022
DOI: 10.2147/idr.s367012
|View full text |Cite
|
Sign up to set email alerts
|

Elevated D-dimer and Adverse In-hospital Outcomes in COVID-19 Patients and Synergism with Hyperglycemia

Abstract: Aim One of the most common laboratory findings in COVID-19 patients has been observed to be hypercoagulability with elevated D-dimer levels. An activation of thrombosis may be generated by hyperglycemia. We aimed to explore the association between D-dimer and in-hospital outcomes, and evaluate the synergistic effect between elevated D-dimer and hyperglycemia on COVID-19 prognosis. Methods A retrospective cohort study was undertaken with 2467 COVID-19 inpatients. D-dimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A recent study to evaluate the effect of hyperglycemia and hypercoagulability on COVID-19 prognosis has shown that elevated hyperglycemia and D-dimer had a synergistic effect on COVID-19 prognosis, and this risk was independent of diabetes history [ 109 ]. In the case of COVID-19, in which physiopathology is characterized by hyperinflammatory response with cytokine overproduction and cardiovascular disorder, it is not yet clear whether the diabetes condition increases the risk of infection or its severity [ 110 ], magnifying the pathogenicity of SARS-CoV-2 since both COVID-19 and diabetes share some pathological mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study to evaluate the effect of hyperglycemia and hypercoagulability on COVID-19 prognosis has shown that elevated hyperglycemia and D-dimer had a synergistic effect on COVID-19 prognosis, and this risk was independent of diabetes history [ 109 ]. In the case of COVID-19, in which physiopathology is characterized by hyperinflammatory response with cytokine overproduction and cardiovascular disorder, it is not yet clear whether the diabetes condition increases the risk of infection or its severity [ 110 ], magnifying the pathogenicity of SARS-CoV-2 since both COVID-19 and diabetes share some pathological mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent review presenting the relationship between DM and COVID-19, it was emphasized that ever since the emerging of the virus, it was observed that patients with DM had a worse outcome when contracting SARS-CoV-2, presenting statistically higher rates of ARDS, organ damage, necessity of hospitalization in ICUs and higher mortality rates, regardless of the geographical area where the studies were performed (53). Some of the most relevant studies regarding the association between DM and COVID-19 that demonstrated the prothrombotic state observed in these patients are summarized in Table I (5,(54)(55)(56)(57)(58)(59).…”
Section: Hypercoagulable Statementioning
confidence: 99%
“…Han et al estimated that D-dimer and fibrinogen were elevated in all COVID-19 patients, so that the concentrations were higher in patients with severe SARS-CoV-2 infection than those in patients with milder forms (46). Similarly, Nopp pointed out that COVID-19 patients developing venous thromboembolism had higher D-dimer levels (47). Several studies described that elevated D-dimer levels correlate with adverse outcomes, and that COVID-19 patients with high values of this parameter should be hospitalized, even if they have no other symptoms, because of the potential risk of thrombosis (48 -50).…”
Section: Laboratory Characteristics Of Hemostatic Disorders In Covid-19mentioning
confidence: 99%